Training Genetic Counsellors to Deliver an Innovative Therapeutic Intervention: their Views and Experience of Facilitating Multi‐Family Discussion Groups. Issue 2 (10th October 2016) - Eisler, Ivan; Flinter, Frances; Grey, Jo; Hutchison, Suzanne; Jackson, Carole; Longworth, Louise; MacLeod, Rhona; McAllister, Marion; Metcalfe, Alison; Patch, Christine; Cope, Buddug; Robert, Glenn; et al.
Abstract: Innovations in clinical genetics have increased diagnosis, treatment and prognosis of inherited genetic conditions (IGCs). This has led to an increased number of families seeking genetic testing and / or genetic counselling and increased the clinical load for genetic counsellors (GCs). Keeping pace with biomedical discoveries, interventions are required to support families to understand, communicate and cope with their Inherited Genetic Condition. The Socio‐Psychological Research in Genomics (SPRinG) collaborative have developed a new intervention, based on multi‐family discussion groups (MFDGs), to support families affected by IGCs and train GCs in its delivery. A potential challenge to implementing the intervention was whether GCs were willing and able to undergo the training to deliver the MFDG. In analysing three multi‐perspective interviews with GCs, this paper evaluates the training received. Findings suggests that MFDGs are a potential valuable resource in supporting families to communicate genetic risk information and can enhance family function and emotional well‐being. Furthermore, we demonstrate that it is feasible to train GCs in the delivery of the intervention and that it has the potential to be integrated into clinical practice. Its longer term implementation into routine clinical practice however relies on changes in both organisation of clinical genetics services and genetic counsellors' professional development.